Chemical and Biological Diversity of the Leaf and Rhizome Volatiles of Acorus calamus L. from Turkey - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
Two different isolation techniques, conventional hydrodistillation (HD) and micro-steam distillation-solid-phase microextraction (MSD-SPME), have been used to analyze the volatile constituents from the leaves and rhizomes of Acorus calamus L. by gas chromatography (GC-FID) and gas chromatography coupled to mass spectrometry (GC-MS). In all the samples studied, phenylpropanoids (16.9-35.3 %) predominated by beta-asarone (15.3-16.3 % in rhizomes, 23.4-31.7 % in leaves) were the main constituent. In addition to phenylpropanoids, the acorane type sesquiterpene acorenone B (7.4-16.4 %) and elemene-type sesquiterpenes, epi-isoshyobunone (3.3-7.3 %) and shyobunone (1.5-4.6 %) were detected among the major volatile constituents in the rhizomes. The monoterpenes were represented by camphor (7.5-13.9 %) and camphene (6.1-7.7 %). In the leaf, myrcene (0.3-7.1 %), limonene (1.0-5.6 %), (Z)-beta-ocimene (2.9-6.1 %) were among the major constituents. Qualitative difference of the volatiles composition in the rhizomes and leaves are discussed as well as of the volatiles obtained by HD and MSD-SPME techniques are discussed. Biological activity tests resulted in moderate anti-acetylcholinesterase effect and significant cupric reducing antioxidant potential of the leaf oil, while the rhizome oil demonstrated relatively lower effects.
Keywords: Acorus calamus; volatiles; beta-asarone; acetylcholinesterase; antioxidant; ACETYLCHOLINESTERASE INHIBITORY-ACTIVITY; ESSENTIAL OIL COMPOSITION; BETA-ASARONE; ANTIOXIDANT CAPACITY; SWEET FLAG; IN-VITRO; PLANTS; ASSAY; IDENTIFICATION; CHROMATOGRAPHY